Abortion Law in Rape Victims' Cases: Perspective of the KUHP and Indonesia's Health Law - Lindawati; Suryono, Arief; Makbul, Ahmad (Jurnal Ilmu Kepolisian, 2025)
Abortion is an issue that is always debated in various parts of the world, including in Indonesia. This study aims to examine the legal aspects of abortion performed on rape victims from the perspective of the latest criminal code, namely Law Number 1 of 2023, and from the perspective of the health law currently in force in Indonesia, namely Law Number 17 of 2023. The theory that focuses on the importance of law for rape victims is the Trauma theory, where trauma is not only an individual event, but also has broad social impacts. This study will examine abortion law from the current perspective of the regulations in force in Indonesia. This study found that there is harmonization in the regulations related to abortion in Indonesia, especially for rape victims. The contribution made by this study is the need for the real implementation of the rules and laws related to rape victims to show that the state is on the side of women. The consequences of rape have been proven to cause mental trauma, worsen the victim's mental condition, and result in physical and psychological suffering for the victim.